2008
DOI: 10.1152/japplphysiol.90466.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in temperature sensation and thermal comfort in humans

Abstract: Sensations evoked by thermal stimulation (temperature-related sensations) can be divided into two categories, "temperature sensation" and "thermal comfort." Although several studies have investigated regional differences in temperature sensation, less is known about the sensitivity differences in thermal comfort for the various body regions. In the present study, we examined regional differences in temperature-related sensations with special attention to thermal comfort. Healthy male subjects sitting in an env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 33 publications
5
126
1
Order By: Relevance
“…Gender differences in thermoregulatory responses exist, particularly in response to heat stress (Cunningham et al 1978;Davies 1979;Havenith 1997;Havenith 2001a:b;Havenith et al 2008;Smith and Havenith 2012) but thermal sensitivity research is generally limited to male participants (Arens et al 2005;Cotter and Taylor, 2005;Nakamura et al 2008;Ouzzahra et al 2012). The present study compared male and female thermal sensation to a 40°C stimulus and overall (mean of rest and exercise), females scored a significantly warmer thermal sensation than males (4.7 ± 1.8 vs 3.6 ± 2.2, p<0.05, respectively).…”
Section: Gender Differencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Gender differences in thermoregulatory responses exist, particularly in response to heat stress (Cunningham et al 1978;Davies 1979;Havenith 1997;Havenith 2001a:b;Havenith et al 2008;Smith and Havenith 2012) but thermal sensitivity research is generally limited to male participants (Arens et al 2005;Cotter and Taylor, 2005;Nakamura et al 2008;Ouzzahra et al 2012). The present study compared male and female thermal sensation to a 40°C stimulus and overall (mean of rest and exercise), females scored a significantly warmer thermal sensation than males (4.7 ± 1.8 vs 3.6 ± 2.2, p<0.05, respectively).…”
Section: Gender Differencesmentioning
confidence: 99%
“…A large body of literature indicates a variety of gender linked differences in physiological responses to cold and heat exposure (Cunningham et al 1978;Davies, 1979;Fournet et al 2013;Havenith, 1997;Havenith 2001a;Havenith et al 2008;Hensel, 1973;Havenith, 2011, 2012) yet research on thermal sensitivity tends to be limited to male participants (Nakamura et al, 2008;Ouzzahra et al 2012;Stevens et al, 1974). Females have been shown to be more sensitive than males to a variety of stimuli (Fillingim et al 1998;Otto and Doygher, 1985;Velle, 1987), yet there is a gap in the literature surrounding gender differences in innocuous thermal sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…limbs). In one of the experiments carried out, Nakamura et al (2008) observed that in heat conditions, local cooling of the face surface has a positive eff ect on thermal comfort for the whole body. Therefore, selective cooling of the head area is an external interference in the mechanisms of thermoregulation, it positively aff ects not only the feeling of comfort for the whole body, but also it also contributes to the reduction of the degree of nuisance of the performed activities.…”
Section: Selection Of the Methods Of Selective Coolingmentioning
confidence: 99%